Conversion of Intermediate Therapies into Intensive Therapies. - Rubén Bembibre Taboada; Carlos Jaime Geroy Gómez; Marcos D. Iraola Ferrer; Julio Cortizo Hernández; Julio Jova Dueñas; Pedro Juan Barrios Fuentes; José Roque Nodal (Medisur)
Background: Intensive care units are dedicated to the prevention, diagnosis and treatment of the physiopathologic conditions that threaten life. Its function in health services is essential. Given the created conditions in the country, it was oriented the conversion of intermediate therapies to intensive therapies. Objectives: to characterize the clinic intensive therapy service ,and to determine its benefits according to the change. Methods: A descriptive and prospective study that characterizes variables of organizing interest and assistance, teaching and administrative results expressed in frequencies, percentages and measures. Results and Conclusions: Human and material resources were distributed; there were 483 admitted with a standard stay of 2,34 days and a necropsia percentage of 95,15%; a total pathological clinic correlation of 96,66%, and partial of 3,34%. The nosocomial sepsis was of 4,5 per 100 patients; people’s satisfaction was of 78,57% with a very well criteria and 21,42% with well. The main cause of attendance was the cerebrovascular disease with 71,84%, with the inclusion of up dated techniques and treatment in its diagnosis. It was observed an adequate morbidity and mobility. It was achieved positive results in teaching and researching fields.